European Research Center for Information Systems (ERCIS): Gründungsveranstaltung Münster, 12. Oktober 2004 - Jörg Becker; Klaus Backhaus; Heinz Lothar Grob; Thomas Hoeren; Stefan Klein; Herbert Kuchen; Ulrich Müller-Funk; Ulrich W. Thonemann; Gottfried Vossen (Westfälische Wilhelms-Universität Münster, European Research Center for Information Systems (ERCIS), 2004)
The European Research Center for Information Systems (ERCIS) was founded on October, 12th 2004. This Working Paper was written with respect to the establishment of ERCIS. Jörg Becker, Managing Director of the ERCIS, writes about fundamental issues of ERCIS. Furthermore all Founding Members write about special issues on IS.
Keywords: 650